Heterosexual Professional Counselors’ Attitudes toward Lesbians and Gay Men: A Brief Social Issues Intervention - Jason R. Kloss (Recent Trends in Arts and Social Studies Vol. 6, 2023)
This quantitative experimental study examined the amenability of attitudes toward lesbian and gay (L.G.) individuals by heterosexual licensed professional counselors (LPCs) after exposure to a brief intervention raising social issues awareness. The social cognitive theory (SCT), which holds that value judgments help to shape a person’s beliefs and motives, served as the theoretical underpinning for this investigation. The general population for this study consisted of LPCs across the nation. The target population for this study consisted of LPCs from ACA, American Mental Health Counselors Association (AMHCA), Counselor Education and Supervision Network (CESNET) Listserv, SurveyMonkey target audience paid service, Facebook, and LinkedIn. The sample consisted of 142 LPCs recruited from professional organizations, listservs, and social media nationwide, evenly divided between an experimental and a control group. Participants from the experimental group were primed using the Social Issues Advocacy Scale. The study hypothesized that LPCs exposed to a brief intervention raising social issues awareness would have greater amenability of attitudes toward L.G. individuals compared to LPCs who were not exposed to the intervention. Findings also showed no statistically significant difference in scores on the survey, as the means of the experimental (M=38.5) and the control (M=37.94) groups differed by less than one point. According to the SCT, the participants in this study were prompted to assess their self-efficacy, personal standards, professionalism, and ambitions after being briefly exposed to social issues or by the instrument itself. This process prompted them to respond to how they felt at the time or how they would prefer to feel in the ideal scenario for improved acceptance of their attitudes. The findings suggested that a brief intervention for raising social issues awareness may not be adequate in changing the attitudes of LPCs about L.G. individuals. This study did not assess attitudes toward other sexual minorities or attitudes of heterosexual LPCs not associated with professional organizations, so these remain areas for future exploration.